Peran TPQ Nurul Iman di Desa Sari Mulyo Kecamatan Sukaraja Kabupaten Seluma dalam Membentuk Generasi yang Beradab, Berakhlak, dan Berkarakter. - Endang Haryanto; Anisa Apri Norma Handayani; Yuke Elpandari; Salwa Tunnisa Islamiyah; Della Nupita Ramadaniya; Fitri Khoirunnisa; Angga Alfarizi; Bastian Pinoci; Mice Yesia Putri; Dwi Nur Sofiyah; Yanda Kurniawan (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
This research examines the role of the Nurul Iman Qur'an Education Park (TPQ) in Sari Mulyo Village in forming a civilized, moral and characterful generation. Islamic education at the elementary level, especially through non-formal institutions such as TPQ, has a crucial role in forming children's character, especially in rural areas which face limited access to formal education. TPQ Nurul Iman focuses on teaching reading and understanding the Koran as well as applying Islamic values in everyday life. This research uses a qualitative comparative approach with data collection methods in the form of direct observation and interviews with teachers and children at TPQ. The research results show that TPQ Nurul Iman not only functions as a center for religious learning but also as a center for character development. Even though it is faced with challenges such as limited facilities and teaching staff and low interest from children, TPQ still makes a significant contribution to the formation of character and morals of children in the village. This research aims to explore the contribution of TPQ in religious education and character development and provide insight for future research and implementation of non-formal education.